2018
DOI: 10.22354/in.v22i4.734
|View full text |Cite
|
Sign up to set email alerts
|

Coxiella burnetii infection in sheep and goats: a public risk health, Colombia

Abstract: Objective. The aim of this study was to provide molecular evidence of C. burnetii in sheep and goats from some herds of Valledupar, Cesar, Colombia. Materials and methods. Fifteen herds of sheep and goats were chosen by convenience to investigate the infection by C. burnetii, during March and April of 2013. 328 female goats and 66 sheep from 15 herds were included in this study. Milk from ewes and vaginal mucus samples from goats were analyzed by Polymerase Chain Reaction for DNA detection of transposase gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…A recent study suggested the circulation of these bacteria in sheep and goats from some herds in Colombia (31) and it highlights the possibility of occurrence of infections in people linked to livestock handling. In the present study, the frequency for C. burnetii was 6.1%, and such figure differs from previous reports about workers in cattle farms of Antioquia (32) and rural workers from Córdoba, in which the researchers found a prevalence of 14.7% and 26.6%, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study suggested the circulation of these bacteria in sheep and goats from some herds in Colombia (31) and it highlights the possibility of occurrence of infections in people linked to livestock handling. In the present study, the frequency for C. burnetii was 6.1%, and such figure differs from previous reports about workers in cattle farms of Antioquia (32) and rural workers from Córdoba, in which the researchers found a prevalence of 14.7% and 26.6%, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Contact with domestic livestock animals, including cattle, goats, and sheep, may represent the main risk for acquiring the infection, as evidence of C. burnetii has been detected in these animals from Colombia [ 95 , 147 ] and their products [ 98 ]. Furthermore, C. burnetii may also be circulating in a wild cycle, as evidence of the bacteria was found among bats that inhabit Macaregua cave, Santander department, Colombia [ 148 ]; thus, cavers and people who perform eco-touristic activities may be aware of the risk that Q fever may represent for them.…”
Section: Coxiella Burnetiimentioning
confidence: 99%
“… 8 Because Q fever was first reported in Colombia in the 1970s, only limited studies focusing on livestock and people with occupational exposure are available. 8 12 These studies found that 25.9% of farmers and 19.5% of their cattle were positive for C. burnetii DNA, and additional serological studies reported exposure in farmers of 31.9%, in slaughterhouse workers of 54%, and in cattle from 27.1% to 60%. 10 12 One study in small ruminants reported C. burnetii DNA in 6% of sheep’s milk and 0.6% of vaginal swabs from goats.…”
mentioning
confidence: 97%
“… 10 12 One study in small ruminants reported C. burnetii DNA in 6% of sheep’s milk and 0.6% of vaginal swabs from goats. 9 Risk factors associated with seropositivity to C. burnetii identified in other studies in Colombian farming communities included tick bites, working with cattle, consuming raw milk products, livestock slaughtering, and keeping hens. 12 …”
mentioning
confidence: 97%